Effect of impurities on the crystal growth from solutions - a new kinetic model - P. M. Martins (2004)
A new approach to the phenomena of impurity adsorption during crystal growth ispresented. We consider that the adsorption of elements onto the active sites of the crystal surfaceis a competitive process between the solute and the impurity molecules. Based on that, a generalequation relating the face growth rates with the supersaturation and the impurity concentration isderived. The main experimental evidences known from the literature on crystal growth kinetics inthe presence of impurities are used to test the proposed model. So far, we conclude that thetheoretical statements of the competitive adsorption model are generally in agreement with theexperimental facts.